Nd2007 2007
DOI: 10.1051/ndata:07558
|View full text |Cite
|
Sign up to set email alerts
|

Resonance data for self-shielding problems

Abstract: Abstract. The investigation of resonance self-shielding effects in macroscopic medium is important for the physics of nuclear reactors and shielding. The degree of consistency of evaluated resonance cross sections data and the requirements to the accurate presentation of self-shielding effects can be estimated by using the simplest benchmark data for resonance averaged functions of neutron transmission and self-indication cross section at arbitrary filter thickness n. We report the developed (for nonfissile nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…to reduce the cement consumption, due to which industries release large quantities of CO 2 , as a contribution to the improvement of healthy environment is becoming increasingly important in the development of sustainable concrete application. Experimental results indicated that the influence of additions, especially slag on frost and de-icing salt resistance of concrete, is not so negative as in the already reported [6].…”
Section: Sustainability 221 Greensupporting
confidence: 46%
“…to reduce the cement consumption, due to which industries release large quantities of CO 2 , as a contribution to the improvement of healthy environment is becoming increasingly important in the development of sustainable concrete application. Experimental results indicated that the influence of additions, especially slag on frost and de-icing salt resistance of concrete, is not so negative as in the already reported [6].…”
Section: Sustainability 221 Greensupporting
confidence: 46%
“…Isotopically enriched samples were kindly loaned by INRNE Sofia [11]. The % enrichments of the Hf in the HfO 2 samples are given in Table 1.…”
Section: Enriched Samplesmentioning
confidence: 99%